Design and Implementation of Distributed Video Live-Streaming System Based on SRS - Wang, Qiang; She, Bo; Cui, Jingru; Qin, Zunying; Li, Guodong (2021 10th International Conference on Educational and Information Technology (ICEIT), 2021)
Since the COVID-19 pandemic, video live-streaming technologies that ensure learning continuity have evolved rapidly. With the epidemic under control in China, a growing number of colleges classroom teaching will be online live simultaneously. Traditional offline teaching will gradually transform to the combination of online and offline mode. With the demand for the normality high-definition online live-streaming, the traditional live broadcast system faces the problems of limited scalability, poor fault tolerant ability and poor user experience. In this paper, a distributed online live-streaming system cross multiple campuses which based on SRS is designed and realized. Through dynamic distributed push, upstream and downstream traffic separation, and multi-level load balancing mechanism, the system can satisfy the need of the automatic and unattended normal video live-streaming teaching of large-scale classrooms. In this loosely coupled system, all components are distributed on each campus and communicate via message queues and HTPP API. The system has been applied to Xi'an Jiaotong University daily online and offline teaching for 700 classrooms spread over three campuses.